AEBP1 Promotes Glioblastoma Progression and Activates the Classical NF-κB Pathway - Kai Guo; Lei Song; Jianyong Chang; Peicheng Cao; Qi Liu (Behavioural Neurology)
Objective. Our study was aimed at investigating the mechanistic consequences of the upregulation of adipocyte enhancer-binding protein 1 (AEBP1) in glioblastoma (GBM). Methods. The expression of AEBP1 in GBM was assessed by bioinformatics analysis and qRT-PCR; the effects of AEBP1 on GBM cell proliferation, migration, invasion, and tumor growth in vitro and in vivo were detected by a CCK-8 assay, colony formation assay, scratch assay, Transwell assay, and subcutaneous tumor formation, respectively. The activation of related signaling pathways was monitored using western blot. Results. Tumor-related databases and bioinformatics analysis revealed that AEBP1 was highly expressed in GBM and indicated poor outcome of patients; its high expression that was also confirmed in GBM tissues and cell lines was closely related to the tumor size. The results of in vitro experiments showed that AEBP1 could significantly promote GBM cell proliferation, migration, and invasion; in vivo experiments suggested that AEBP1 could contribute to the growth of GBM tumors. AEBP1 could upregulate the level of IκBα phosphorylation, decrease IκBα expression, activate the NF-κB signaling pathway, and promote the expression of downstream oncogenes. Conclusion. Upregulated AEBP1 in GBM promotes GBM cell proliferation, migration, and invasion and facilitates tumor growth in vivo by activating the classical NF-κB pathway.